Pulled by God: Sound and Altered State of Consciousness in the Hälqä-Sohbät Ritual of Uyghur Sufis - Mu, Qian (European Journal of Musicology, 2022)
In Xinjiang, northwestern China, the Uyghur Sufi Muslims practice a localised samāʿ ritual called hälqä-sohbät, which involves dhikr, singing and dancing. Participants in hälqä-sohbät sometimes enter an altered state of consciousness called jäzba, which literally means pulled by God. The hälqä-sohbät includes various sounds such as the singing of hikmät, muqam and mäshräp, as well as instrument playing. However, Uyghur Sufis often deny the role of sound as a decisive factor in triggering jäzba, but attribute its causation to the practice of dhikr, especially silent dhikr. Based on ethnographic data from Khotan, southern Xinjiang, and inspired by Leman’s research framework for music, gesture and embodied meaning, I study the relationship between sound and jäzba in hälqä-sohbät in three perspectives: a first-person perspective from the point of view of the practitioners; a second-person perspective in which hälqä-sohbät is viewed as a way of social interaction in a “me to you” way; and a third-person perspective in which I, the researcher, try to disclose and analyse the various factors at work in triggering the altered state of consciousness, such as timbre, rhythm, and physical movements.